1984
DOI: 10.1111/j.1439-0485.1984.tb00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Certain Organic Substances on Growth and Colony Formation of Asterionella glacialis Castracane (Bacillariophyceae)

Abstract: Abstract. Organic substances are suspected to influence the unpredictable, episodic blooms which characterize the planktonic pennate diatom Asterionella glacialis in certain coastal waters. Experiments to test its general responsiveness to organic enrichments in terms of growth rate and colony formation were carried out. An axenic clone was grown at 10° C, 0.039 l min‐1,12:12 LD cycle in Guillard's f/2 medium enriched with eight different organic substances. Growth rates in organically‐enriched media during e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The addition of vitamins mixture* (B12, biotin and thiamine) and inorganics nutrients* (NO3, Si, P04 and trace metals) to the filtrate had no apparent additional effect on the algal growth. According to Teng (1984) who has prepared an axenic culture of the same species which has low (10°C) optimal growth temperature, the higher yield of this alga was attained with organic substances such as glycylglycine, trypticase and yeast extract. However, we have obtained the results that the algal growth has been little affected by addition of trypticase peptone, glycine, glycylglycine, and proline, respectively (Table 1).…”
Section: Growths Of the Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of vitamins mixture* (B12, biotin and thiamine) and inorganics nutrients* (NO3, Si, P04 and trace metals) to the filtrate had no apparent additional effect on the algal growth. According to Teng (1984) who has prepared an axenic culture of the same species which has low (10°C) optimal growth temperature, the higher yield of this alga was attained with organic substances such as glycylglycine, trypticase and yeast extract. However, we have obtained the results that the algal growth has been little affected by addition of trypticase peptone, glycine, glycylglycine, and proline, respectively (Table 1).…”
Section: Growths Of the Bacteriamentioning
confidence: 99%
“…Kain and Fogg (1958) failed to make the axenic culture of the same species isolated from the Hamble River, and suggested that growth of the unaxenic alga requires some organic substances derived from concomitant bacteria. Recently Teng (1984) showed that an axenic A. glacialis isolated from Narragansett Bay was positively responsive to elevated levels of certain organic substances such as 100 mg 1-1 of trypticase peptone + 100 mg 1-1 yeast extract, or 100 mg 1-1 glycylglycine. However, he did not achieved the further experiments on the nutrient requirements.…”
Section: Introductionmentioning
confidence: 99%